The Influence of Transformational Leadership and Organizational Culture on Employee Performance Through Organizational Commitment - Asrul, Asrul; Jusriadi, Edi; Anggoro, M. Yusuf Alfian Rendra (Borong Newinera Publisher, 2025)
Human resources (HR) play an important role in the success of an organization, including in the government sector such as the Sinjai Religious Court. Optimal employee performance reflects the effectiveness of the organization and is the main indicator of quality public service. This study aims to analyze the effect of transformational leadership and organizational culture on employee performance, with organizational commitment as a mediating variable. The study used a quantitative approach with a survey method, and sampling was carried out using a saturated sampling technique, involving the entire population of 49 respondents. The data analysis technique used the Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) through SmartPLS 4.0 software. The results of the analysis showed that transformational leadership had a positive and significant effect on organizational commitment with a P-Value of 0.043 <0.05. This finding indicates that the characteristics of transformational leaders such as inspiration, individual attention, and intellectual stimulation can increase employee commitment. However, interviews with employees indicated that performance was more determined by compliance with work procedures and professionalism, rather than direct direction from the leader. This shows that the influence of leadership on performance is not proven to be significant directly, but has more impact through increasing organizational commitment. Transformational leadership can indirectly strengthen employee performance through increased organizational commitment, especially in institutions that have formal and standard work systems.